2012
DOI: 10.1073/pnas.1121588109
|View full text |Cite
|
Sign up to set email alerts
|

Spatial navigation impairment is proportional to right hippocampal volume

Abstract: Cognitive deficits in older adults attributable to Alzheimer's disease (AD) pathology are featured early on by hippocampal impairment. Among these individuals, deterioration in spatial navigation, manifested by poor hippocampus-dependent allocentric navigation, may occur well before the clinical onset of dementia. Our aim was to determine whether allocentric spatial navigation impairment would be proportional to right hippocampal volume loss irrespective of general brain atrophy. We also contrasted the respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
106
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 36 publications
14
106
0
6
Order By: Relevance
“…This might be explained by the critical role of right hippocampus in navigation [43]. It has been suggested that this role may be more prominent when cognitive impairment is present [44]. Alternatively, the right-sided findings may be due to asymmetric neurodegeneration and reorganization of neuronal motor pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the critical role of right hippocampus in navigation [43]. It has been suggested that this role may be more prominent when cognitive impairment is present [44]. Alternatively, the right-sided findings may be due to asymmetric neurodegeneration and reorganization of neuronal motor pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, transgenic mice expressing human amyloid precursor protein and patients with mild cognitive impairment with the predicted pathology of Alzheimer’s disease show similar impairments on analogous versions of an allocentric Morris Maze (Possin et al, 2016). Performance on an allocentric Morris Maze correlates with right hippocampal volumes in patients with amnestic mild cognitive impairment or Alzheimer’s disease (Nedelska et al, 2012) and with the size of CA1 hippocampal lesions in acute transient global amnesia (Bartsch et al, 2010). In functional neuroimaging studies, the medial temporal lobe activates in relationship to the spatial layout of virtual environments (Aguirre et al, 1996; Maguire et al, 1998; Mellet et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent study reported that the genetic risk factor for late-onset AD - apolipoprotein E e4 allele, which is frequently analyzed in clinical trials - further exacerbated spatial navigation impairment in aMCI patients [8]. The most recent study revealed that the right hippocampus was responsible for allocentric navigation impairment in prodromal AD [9], especially in subjects with cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%